Thoracotomy compared to laparotomy in the traumatic diaphragmatic hernia. Systematic review and proportional methanalysis - Silva,Gracilene Pinheiro (2018)
Abstract Purpose: To evaluate the most used approach to treat traumatic diaphragmatic ruptures, and in which one the requirement to assess the second cavity is more frequent. Methods: Systematic review, observational studies. Outcomes: moment of approach, most commonly via addressed and the requirement to open the other cavity. Bases searched: Lilacs, Pubmed, Embase, Clinicaltrials.gov and Web of Science. Statistical analysis: StatsDirect 3.0.121 software. Results: Sixty eight studies (2023 participants) were included. Approach in acute phase was performed four times more than in chronic phase. Approach: abdominal 65% (IC 95% 63-67%), thoracic 23% (IC 95% 21-24%), abdominal in the acute phase 75% (IC 95% 71-78%), and chronic 24% (IC 95% 19-29%), thoracic in the acute phase 12% (IC 95% 10-14%) and chronic 69% (IC 95% 63-74%). Thorax opening in the abdominal approach: 10% (95% CI 8-14%). Abdomen opening in the thoracic approach: 15% (95% CI 7-24%). Conclusions: The most common approach was the abdominal. The approach in the acute phase was more common. In the acute phase the abdominal approach is more frequent than the thoracic approach. In the chronic phase the thoracic approach is more frequent than the abdominal one. The requirement to open the second cavity was similar in both approaches.